2021
DOI: 10.1038/s41597-021-00983-y
|View full text |Cite
|
Sign up to set email alerts
|

Global data set of long-term summertime vertical temperature profiles in 153 lakes

Abstract: Climate change and other anthropogenic stressors have led to long-term changes in the thermal structure, including surface temperatures, deepwater temperatures, and vertical thermal gradients, in many lakes around the world. Though many studies highlight warming of surface water temperatures in lakes worldwide, less is known about long-term trends in full vertical thermal structure and deepwater temperatures, which have been changing less consistently in both direction and magnitude. Here, we present a globall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Unlike previous studies on sediment bacterial communities in Lake Bosten, which indicated that WT variations weakened interspecific competition and increased the relative abundance of certain bacteria ( Zhang et al, 2020 ), the microbial communities in the water were more influenced by WT fluctuations. Surface water, in particular, is highly susceptible to environmental factors due to its direct exposure to the external environment at the water-air interface ( Pilla et al, 2021 ). Significant changes in atmospheric temperature can have cascading effects on plankton growth rates, lake primary productivity, and the physical and chemical environment of the lake ( Lewandowska et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies on sediment bacterial communities in Lake Bosten, which indicated that WT variations weakened interspecific competition and increased the relative abundance of certain bacteria ( Zhang et al, 2020 ), the microbial communities in the water were more influenced by WT fluctuations. Surface water, in particular, is highly susceptible to environmental factors due to its direct exposure to the external environment at the water-air interface ( Pilla et al, 2021 ). Significant changes in atmospheric temperature can have cascading effects on plankton growth rates, lake primary productivity, and the physical and chemical environment of the lake ( Lewandowska et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2015) for LSWT and Pilla et al. (2021) for water temperature profiles, manual sampling was typically scheduled in the morning and in the early afternoon, with a time frequency that ranged from daily to monthly with sporadic cases in which water temperature was sampled twice daily, in the morning and in the evening (Noges & Noges, 2014). Due to technological and automation advancements, mercury thermometers have been progressively replaced by digital thermometers and/or multi‐parametric probes, and manual sampling replaced by automatic sampling using buoys equipped with surface sensors (e.g., Austin & Colman, 2007) or moored stations equipped with thermistor chains providing water temperature measurements at discrete depths (Tiberti et al., 2021; Valerio et al., 2012).…”
Section: Water Temperature Monitoring Approachesmentioning
confidence: 99%
“…Indeed, water temperature is one of the most widely monitored physical characteristic of lakes. Most lake temperature records start during the second half of the 20th century or in the 21st century, although for some lakes regular measurements of water temperatures are available for even a longer period (see e.g., some Austrian lakes, Dokulil et al, 2006;Livingstone & Dokulil, 2001; some lakes in the English Lake District, Feuchtmayr et al, 2012; Lake Peipsi in Estonia/Russia, Kangur et al, 2020Kangur et al, , 2021; Lake Mendota in the USA Robertson, 2016; see also Pilla et al, 2021). The relatively large availability of lake water temperature observations is due to both (a) the relative ease and affordability of acquiring this type of measurement and (b) the central role of water temperature in controlling most of the physical and bio-chemical processes in a lake (Mollema & Antonellini, 2016;Woolway, Kraemer, et al, 2020).…”
mentioning
confidence: 99%